Alternatif Peningkatan Ruas Jalan Dengan Pendekatan Manajemen Lalu Lintas Jalan Abdullah Daeng Sirua Dan Jalan Adyaksa Baru - Pertiwi, Elsa Putri; Nurdin, Abd. Rahim; Yunianti, Nurhadijah (Program Studi Teknik Sipil Universitas Bosowa, 2025)
The increasing population in Makassar City each year has led to a rise in the number of motor vehicle drivers. This study aims to analyze intersections and provide solutions. At the T-junction of Jalan Abdullah Daeng Sirua and Jalan Adyaksa Baru, delays arise due to side obstacles, including vehicles entering and exiting from Jalan Inspeksi Kanal, as well as the presence of restaurants, businesses, and service providers along the intersection’s edges. Limited parking spaces cause many vehicles to stop haphazardly. Another cause of congestion at this intersection is the narrow Daeng Sirua Bridge, which creates traffic jams along the stretch of road at the T-junction of Jalan Abdullah Daeng Sirua and Jalan Adyaksa Baru. To address these issues, solutions include road widening, bridge expansion, and reconfiguration of traffic lights at the intersection. The Level of Service (LOS) at the current conditions shows Approach Code A (Jalan Abdullah Daeng Sirua) rated as D, Approach Code B (Jalan Abdullah Daeng Sirua) rated as F, and Approach Code C (Jalan Adyaksa Baru) rated as C.